SARS-CoV-2 infection risk is higher in vaccinated patients with inflammatory autoimmune diseases or liver transplantation treated with mycophenolate due to an impaired antiviral immune response: results of the extended follow up of the RIVALSA prospective cohort - Rizzi, Manuela; Tonello, Stelvio; Brinno, Cristiana; Zecca, Erika; Matino, Erica; Cittone, Micol; Rizzi, Eleonora; Casciaro, Giuseppe Francesco; D’Onghia, Davide; Colangelo, Donato; Minisini, Rosalba; Bellan, Mattia; et al. (Frontiers in Immunology, 2023)
Background: A relevant proportion of immunocompromised patients did not reach a detectable seroconversion after a full primary vaccination cycle against SARS-CoV-2. The effect of different immunosuppressants and the potential risks for SARS-CoV-2 infection in these subjects is largely unknown. Methods: Patients from the Rivalsa prospective, observational cohort study with planned anti SARS-CoV-2 third dose mRNA vaccination between October and December 2021 were asked to participate to this follow-up study. Patients were asked about eventual confirmed positivity to SARS-CoV-2 infection within 6 months from the third dose and to undergo a blood draw to evaluate seroconversion status after the additional vaccine shot. Results: 19 out of 114 patients taking part in the survey developed a confirmed SARS-CoV-2 infection; we identified mycophenolate treatment as an independent predictor of an increased risk of infection even after the third vaccine dose (OR: 5.20, 95% CI: 1.70-20.00, p=0.0053). This result is in agreement with the in vitro evidence that MMF impairs both B and T lymphocytes driven immune responses (reduction both in memory B cells producing anti-spike antibodies and in proliferating CD4+ and CD8+ T cells). Conclusions: Immunocompromised patients need an additional vaccine administration to reach a detectable seroconversion, thus fostering a more personalized approach to their clinical management. Moreover, patients undergoing mycophenolate treatment show a specific increased infection risk, with respect to other immunosuppressants thus supporting a closer monitoring of their health status.